India needs to act fast against the stroke epidemic: a tactical and radical change needed - Gupta, Geeta Y.; Gupta, Yogesh A. (International Journal Of Community Medicine And Public Health, 2025)
In India stroke is the 4th leading cause of mortality and 5th leading cause of disability. The mean age of onset of stroke in India is lower than in western countries, and even the incidence in the young population is high in India. When we performed the review of literature, we found there are two different sets of countries in the world. Historically, one set of countries has adopted the best national policies with an aim to reduce mortality, morbidity, and disability in patients. Then there is another set of countries like India, which has fought this epidemic in a fragmented manner and so is still looking at a huge stroke burden. To understand this divide, we studied the history and present format of the fight and then compared it to that of India. Finally, we can outline areas that require improvement. This article suggests a tactical and radical change in the fight against stroke. India needs to ACT FAST to prevent the damage because of stroke. To write this review, we wanted to understand the historical background of stroke, so we conducted an extensive review of articles with keywords, studied the way trials on tissue plasminogen were done, how CT scan discovery made the difference, and since then, how developed countries have made progress. Then we studied the present Indian situation and the actual root cause of high mortality and disability in Indian stroke patients. We then reviewed how developed countries plugged their gaps.